2020
DOI: 10.1681/asn.2019080827
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Mechanisms of Kidney Injury in 2,8-Dihydroxyadenine Nephropathy

Abstract: BackgroundHereditary deficiency of adenine phosphoribosyltransferase causes 2,8-dihydroxyadenine (2,8-DHA) nephropathy, a rare condition characterized by formation of 2,8-DHA crystals within renal tubules. Clinical relevance of rodent models of 2,8-DHA crystal nephropathy induced by excessive adenine intake is unknown.MethodsUsing animal models and patient kidney biopsies, we assessed the pathogenic sequelae of 2,8-DHA crystal-induced kidney damage. We also used knockout mice to investigate the role of TNF rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 70 publications
(105 reference statements)
6
60
0
Order By: Relevance
“…Tumor growth factor-β (TGF-β), produced at least in part by epithelial cells, and infiltrated macrophages then activate interstitial fibroblasts to produce extra cellular matrix. Recently, it was shown that TNFR-1 (TNF receptor 1) knockout mice were protected from 2,8-DHA nephropathy, suggesting that TNFR1 antagonism could be a potential future target for APRT deficiency in human [44]. Here, we demonstrate that AhR knockout mice are also protected from 2,8-DHA nephropathy.…”
Section: Discussionsupporting
confidence: 54%
“…Tumor growth factor-β (TGF-β), produced at least in part by epithelial cells, and infiltrated macrophages then activate interstitial fibroblasts to produce extra cellular matrix. Recently, it was shown that TNFR-1 (TNF receptor 1) knockout mice were protected from 2,8-DHA nephropathy, suggesting that TNFR1 antagonism could be a potential future target for APRT deficiency in human [44]. Here, we demonstrate that AhR knockout mice are also protected from 2,8-DHA nephropathy.…”
Section: Discussionsupporting
confidence: 54%
“…Nonetheless the growing consensus is that resident fibroblasts, pericytes and bone marrow derived cells are the main precursors of myofibroblasts in the kidney and contribute to renal fibrosis in a similar proportion. 4,10,29,[33][34][35] Resident fibroblasts and pericytes express the platelet derived growth factor receptor β (PDGFR-β) and are one of the most numerous cell types in the kidney. 4,9,31,36 A recent study also confirmed PDGFR-β + cells as the main precursors for myofibroblasts in human kidneys.…”
Section: Introductionmentioning
confidence: 99%
“…Adenine nephropathy is a chronic damage model with strong parallels to human crystal induced pathologies, whilst UUO is an acute damage model for mechanical stress. 29,33,[42][43][44] Using the highly specific RNAscope® in-situ hybridization method allowed the colocalization of target and marker mRNAs down to a single cell resolution. In these pathological models the effects of TGFβ-R2 deletion in PDGFR-β + cells on the expression of α-SMA as a marker for myofibroblast formation was examined.…”
Section: Introductionmentioning
confidence: 99%
“…Adenine-induced kidney disease in mice is frequently used as an experimental animal model of CKD [ 4 , 9 , 25 , 26 ]. Mechanistically, orally administered adenine (a purine base) is converted into an insoluble nephrotoxic byproduct 2,8-dihydroxyadenine (2,8-DHA) that forms tubulointerstitial crystals and causes renal inflammation and fibrosis [ 27 ]. We have previously reported that germ-free (GF) mice showed more severe adenine-induced kidney damage than specific-pathogen-free (SPF) mice with normal microbiota [ 15 ]; however, the underlying mechanism for this has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%